Eliminación de la justicia penal militar en la Policía Nacional de Colombia en el posconflicto (2018)
The main objective of this paper is to question the National Police of Colombia as being part of the military justice in post-conflict situations with an adaptation or correspondence from some supports and foundations of the analytical categories and theoretical elements of legal sociology. Currently, its uniformed members who are on active duty may be investigated and prosecuted by the Military Criminal Justice when they commit offenses in relation to police duties. Once the armed conflict ceases, the creation of a special justice is proposed that is part of the ordinary criminal justice, it could even be operated by retired members of the National Police. But nothing prevents that for these uniformed police officers the judges are the same as those for other Colombians, provided all the social, legal, factual and other psychosocial aspects that can be involved are taken into account when these special public servants are being investigated, accused or judged.